Factors Influencing Audit Judgment: Experience, Pressure, Complexity, Expertise, and Ethics in Public Accounting - Ritonga, Pardomuan (Institut Bisnis dan Informatika Kesatuan, 2025)
The reliability of financial statements has become increasingly important in supporting business decision-making and maintaining public trust, thereby highlighting the critical role of auditors in making professional judgments. This study aims to examine the influence of auditor experience, obedience pressure, task complexity, audit expertise, and professional ethics on audit judgment. Primary data were obtained through questionnaires distributed to public accounting firms, with respondents including auditors at various hierarchical levels, such as senior auditors, supervisors, managers, and partners. The findings indicate that auditor experience, obedience pressure, task complexity, and audit expertise significantly enhance the quality of audit judgments. Considerations play an important role in auditors’ evaluative processes. Furthermore, the coefficient of determination analysis shows that 38.5% of the variation in audit judgment can be explained by these factors, while the remaining 61.5% is influenced by other variables not addressed in this study. These results underscore the complex nature of audit judgment and the necessity of considering multiple dimensions, including experience, expertise, task complexity, adherence to ethical standards, and organizational pressures, when evaluating auditor decision-making.